Soil Hydraulic Modeling Outcomes with Four Parameterization Methods: Comparing Soil Description and Inverse Estimation Approaches - Graham, S.L. (2020)
This study investigated, for a heterogeneous stony soil, four methods of soil hydraulic parameterization: (i) use of a pedotransfer function with a four‐layer soil profile based on detailed soil physical and textural description; (ii) use of a pedotransfer function with a single‐layer soil description; (iii) inverse estimation from soil moisture data; and (iv) inverse estimation from lysimeter drainage. Soil drainage, volumetric water content, and evapotranspiration were each modeled using HYDRUS‐1D for an irrigated pasture in New Zealand during the time period 1 July 2011 to 15 Mar. 2014. The first 15 mo were used for model spin‐up and inverse parameter estimation, while the remainder of the study period was used as a validation period, during which model results were compared against field data. Predictions from each model parameterization were compared with field‐measured fluxes from lysimeter, soil moisture sensors, and eddy covariance to determine the approach most appropriate for our site and application.